Should brief interventions in primary care address alcohol problems more strongly?. (22nd November 2013) - McCambridge, Jim; Rollnick, Stephen
Abstract Background Brief interventions have well‐established small effects on alcohol consumption among hazardous and harmful drinkers in primary care, and national large‐scale programmes are being implemented in many countries for public health reasons. Methods This paper examines data from reviews and draws upon older brief intervention studies and recent developments in the literature on motivational interviewing to consider the capacity of brief interventions to benefit those with problems, including those with severe problems. Results Effects on alcohol problems have been shown much less consistently, and evidence cannot be claimed to be strong for any outcomes other than reduced consumption. Combinations of advice and motivational interviewing are a promising target for evaluation in trials, and more detailed studies of the conduct of brief interventions are needed. Conclusions We propose that brief interventions in primary care may be more effective if they offer appropriate content in a person‐centred manner, addressing patient concerns more directly.